Sosialisasi Aplikasi Berbasis Web sebagai Media Pencegahan Obesitas pada Remaja di SMA Negeri di Kabupaten Kerinci - Nasrazuhdy, Nasrazuhdy; Agraini, Agraini; Nopindra, Alpari; Saquro, Abdan (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2022)
Obesity can be defined as excessive or abnormal accumulation of fat in the body that can interfere with health. Obesity and overweight are said to be more associated with global causes of death than the incidence of underweight. (WHO: 2011). Obesity adversely affects almost all physiological functions of the body and constitutes a significant public health threat. This increases the risk of developing disease conditions, such as diabetes mellitus, cardiovascular disease, some types of cancer, various musculoskeletal disorders and poor mental health, all of which have negative effects on quality of life, work productivity and health care costs. (Muhammad Dicky Setyawan et al, 125: 2020) . Based on the basic health profile in 2013 it can be seen that obesity in adolescents nationally also increases every year. The average obesity sufferer in 2007 was 10.3%, increasing to 15.4% in 2013. (D. Wulandari: 2019)